Separation of power - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2020)
With CIA director Thomas Stansfield dead, his protégé, Dr. Irene Kennedy, is poised to take over the reins of the agency, while CIA operative Mitch Rapp heads to the Middle East to try to stop the chaos that could ignite World War III.